Exploring and classifying the transient radio sky - Pietka, M (2016)
Observations of the transient radio sky provide an insight into the most dynamic and energetic events in the Universe. The exploration of transient and variable sources, for a long time primarily focused on higher frequencies, has recently been extended to the long wavelength regime, with the development of facilities such as the Low Frequency Array (LOFAR). In this work I describe the general design of LOFAR as well as details of the commissioning work performed during the early stages of operation. Secondly, I perform an analysis of the first dedicated LOFAR transient survey -- the Radio Sky Monitor. The investigation is focused on exploring 30 seconds time-scale images and allows us to place an upper limit on the expected areal densities of fast radio transients in the low frequency sky. It also provides spectral index constraints on the previously found, first LOFAR transient event. I also investigate the relation between the radio luminosities and variability time-scales across a wide range of sources – from nearby flare stars to distant supermassive black holes. The results are discussed in context of the potential use as a classification method, as well as in comparison with the expected brightness temperature of the events. The relation is used as a base for building a tool which classifies (with a given probability) an observed event, depending on the measured rise/decline rates of the flare. It includes the automatic selection of flares and takes into account the estimated areal densities of different classes of objects. Lastly, I discuss the results of the luminosity – time-scale correlation in context of the estimation of the kinetic power, as well as future prospects of implementing the presented classification method into an automated transient detection pipeline for instruments such as MeerKAT and the Square Kilometer Array.